تخطيط قلب الجنين أثناء المخاض - يوسف, أحمد حسن; صالح, حسن; عبد الحميد, ميمون (Latakia University Journal -Medical Sciences Series, 2019)
تضمنت هذه الدراسة 150)) ماخضاً أجري لهن تخطيط قلب الجنين في أثناء المخاض وتحليل معطيات التخطيط مع التركيز على الترددية والتباطؤات وتقييم أبغار الوليد خلال الدقيقة الأولى والدقيقة الخامسة وإجراء معايرة (PCO2 , PO2 , Be , PH) من الوريد والشريان السريين وكانت النتائج كالآتي: 1 ـ إن التخطيط الشامل لحالة قلب الجنين وتقييمه بحسب المشعر المتكامل (كريبس أو المعدل) تعكس حالة الجنين الجيدة بنوعية عالية وصلت حتى 99% بينما لم تزل الحساسية متدنية (كريبس 30 %، يوسف 67%) ويستدل على ذلك من تحليل الوسط الاستقلابي لدم الشريان السري. 2 ـ إن الأكثر سوءاً بالنسبة إلى حالة الجنين هو ظهور التباطؤات المتغايرة غير النموذجية, ويليها ظهور التباطؤات المتأخرة DIP II حيث كان متوسط PH الشريان السري 7.15 ± 1.02 . 3 ـ إن قيم شدة التردد (3ـ5) تدل على حالة جنين سيئة وكان متوسط PH الشريان السري 7.06 ±0.54. 4 ـ إن وجود فترات يقظة طويلة على تخطيط قلب الجنين الكهربائي مع نسبة يقظة إلى النوم > 2.9 ذات دلالة سيئة على حالة الجنين وكان متوسط PH الشريان السري < 7.17 . This study included 150 parturients. Intrapartum fetal monitoring, Apgar score in 1th and 5th minute, and titrating (Be – PCO2 – PO2 – PH) from umbilical vein and artery were performed. The results were as follows: 1 – A comprehensive analysis of CTG by Krebs or modified score reflected its normal state with high specificity (99%) and low sensitivity (Krebs 30%, Yossef 67%). 2 – The most harmful pattern for fetuses was the appearance of DIP III on fetal monitoring, followed by DIP II with the average PH for umbilical artery being (7.15 ± 1.02). 3 – The ratios of ability variability (3–5) reflected a bad fetal state, with the average PH for umbilical artery being (7.06 ± 0.54). 4 – The appearance of a long period of wakefulness on fetal monitoring with a rate of wakefulness to sleep being more than 2.9; this represented a bad sign for the fetus state, with the average PH of the blood in the umbilical artery being < 7.17.